Wearable and Hand-Held Haptics - Prattichizzo, Domenico; Otaduy, Miguel; Kajimoto, Hiroyuki; Pacchierotti, Claudio (IEEE transactions on haptics, 2019)
The papers in this special section examine the technology of wearable and hand-held haptic devices. These papers reflect several key directions in current research in this area. Researchers and engineers are devising new ways to better overcome the intrinsic limitations of these types of haptic interfaces, exploiting a renewed understanding of the perceptual basis of haptics and an improvement in the available design and manufacturing techniques. We expect knowledge in this area to continue to grow, thanks to the fertile interactions between activities in mechatronics, ergonomics, robotics, and haptics, as well as for the need for wearable and hand-held haptics driven by fast-growing applications such as gaming, rehabilitation, training, and medicine.